1994
DOI: 10.1002/mrc.1260321210
|View full text |Cite
|
Sign up to set email alerts
|

Influence of skeletal alteration of lignoids on carbon‐13 NMR chemical shifts

Abstract: The characteristic 13C NMR chemical shift ranges as a guide for the establishment of the parent skeletons of various categories and subcategories of lignoids (lignans, neolignans and oxyneolignans) and for the determination of the substitution pattern of the side‐chain are tabulated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 141 publications
0
5
0
Order By: Relevance
“…The radical cyclisation route utilised for the synthesis of tetrahydrofuran lignans [eqn. (20), see Section 2.31 has been extended to the synthesis of sesamin and eudesmin (Scheme 8). I8O A review of the acrobatic rearrangement reactions of furofurans which attempts to rationalise the mechanisms of many of the acid-catalysed, oxidative and reductive reactions they undergo has been published.18' No attempt is made here to catalogue all of the known arylnaphthalene derived lignans.…”
Section: )'76'77mentioning
confidence: 99%
“…The radical cyclisation route utilised for the synthesis of tetrahydrofuran lignans [eqn. (20), see Section 2.31 has been extended to the synthesis of sesamin and eudesmin (Scheme 8). I8O A review of the acrobatic rearrangement reactions of furofurans which attempts to rationalise the mechanisms of many of the acid-catalysed, oxidative and reductive reactions they undergo has been published.18' No attempt is made here to catalogue all of the known arylnaphthalene derived lignans.…”
Section: )'76'77mentioning
confidence: 99%
“…Seven lignans (1 ± 7; Fig. 1) were identified by comparison with previously reported spectroscopic data [3], [4], [5], [6], [7], [8], [9], [10], [11], [12].…”
mentioning
confidence: 72%
“…Bioassay-guided fractionation of the methanolic extract of M. thunbergii bark revealed that the CH 2 Cl 2 fraction was the most active one (65.7 % protection against glutamate-induced toxicity at 1 mg/mL, p < 0.01). Further fractionation and separation of the CH 2 Cl 2 fraction by several chromatographic methods yielded seven compounds ( Fig.1) identified as (±)-isoguaiacin (1), mesodihydroguaiaretic acid (2), machilin A (3), (+)-galbelgin (4), licarin A (5), (±)-sesamin (6), and (+)-guaiacin (7) by the direct comparison of their physicochemical and spectroscopic data with those previously reported [3], [4], [5], [6], [7], [8], [9], [10], [11], [12].…”
mentioning
confidence: 73%
“…Both ! H and 13 C (37) NMR spectroscopy are useful and complementary methods; indeed the 13 C NMR spectroscopy of lignans has been the subject of extensive reviews (32,33).…”
Section: Structural Elucidation Of Lignans and Neolignansmentioning
confidence: 99%